Biochemical abnormalities among patients referred for celiac disease antibody blood testing in a primary health care setting - Kårhus, Line Lund; Kriegbaum, Margit; Grand, Mia Klinten; Lind, Bent Struer; Møllehave, Line Tang; Rumessen, Jüri J.; Andersen, Christen Lykkegaard; Linneberg, Allan (Scientific reports, 2022)
To investigate possible biochemical abnormalities associated with celiac disease (CD) antibody positivity in a primary health care setting and thereby identify predictors that could potentially reduce diagnostic delay and underdiagnosis of CD. This observational cohort study included measurements of CD antibodies in the Copenhagen Primary Care Laboratory (CopLab) database from 2000 to 2015; CD antibody positivity was defined as tissue transglutaminase antibody IgA or IgG ≥ 7 kU/L and/or deamidated gliadin peptide antibody IgG ≥ 10 kU/L. Individuals with a prior diagnosis of CD were excluded. We examined differences between individuals with positive and negative CD antibody tests regarding the results of biochemical tests performed six months before and one month after the date of the CD antibody test. We identified 76,265 measurements of CD antibodies during 2000–2015, and 57,061 individuals met the inclusion criteria (706 antibody-positive and 56,355 antibody-negative). We found lower ferritin, hemoglobin, cobalamin and folic acid levels and higher levels of transferrin, ALAT (alanine transaminase), and alkaline phosphate among individuals with a positive CD antibody test. Furthermore, we illustrated more measurements below the sex-specific reference intervals for hemoglobin, mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC), ferritin, cobalamin and folic acid among individuals with a positive CD antibody test. This study identified several biochemical abnormalities associated with CD antibody positivity among individuals referred to CD antibody testing. The pattern of abnormalities suggested that micronutrient deficiencies were prevalent among CD antibody-positive individuals, confirming malabsorption as a sign of CD. These findings illustrate the possibility of reducing diagnostic delay and underdiagnosis of CD.